Relationship between Husband’s Support and Mother’s Work and Exclusive Breastfeeding - Fauzianty, Ariska; Fitriahadi, Enny (Universitas Muhammadiyah Semarang, 2022)
Exclusive breastfeeding is one of the goals of Sustainable Development Goals (SDGs) in ending all the forms of mallnutrition. Exclusive breastfeeding coverage in DI Yogyakarta is still loer than the targer, this is based on lack of husband support and mother’s work. The purpose of this study was to analyze the correlation between mothers’ occupation and husbands’ support and exclusive breastfeeding. The study was quantitative method with cross sectional approach. The samples were 52 people which were taken using purposive sampling. The measurement tool was questionnaire and the data were analyzed using Chi Square. Based on the result of the study, it was found that almost all mothers who do not work give exclusive breastfeeding (77,8%), and all mothers who received support from their husbands gave exclusive breastfeeding (100%). The probability value (p) was 0.026 and p= 0.015. In conclusion, there is a correlation between mothers’ occupation and husbands’ support and exclusive breastfeeding. Working mothers are suggested to understand breastmilk management (how to pump breast milk, how to give pumped milk to the baby, and how to keep breast milk in freezer) and utilize lactation room in their working place as well as involving husbands in counselling activites about the importance of exclusive breastfeeding.